A composite amine catalyst and its preparation method and application

By using composite amine catalysts to regulate the reaction process and segment distribution, the problem of permanent deformation of low-density elastic polyurethane foam compression is solved, and better mechanical properties and stability are achieved.

CN119751791APending Publication Date: 2025-04-04FOSHAN PUJIA CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411968738.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Low-density elastic polyurethane foam is difficult to fully restore its original shape after compression, resulting in a large permanent deformation of the compression and cannot meet the actual use needs.

Method used

A composite amine catalyst is used, including tertiary amines, organic acids, 1,8-diazabicyclo[5.4.0]undec-7-ene salts and small molecule polyols. By regulating the process of blowing reaction and gel reaction, a suitable distribution of urethane segments and urea segments is formed to construct a tight network structure to weaken the creep effect of hydrogen bonds.

Benefits of technology

It significantly reduces the compression permanent deformation of low-density elastic polyurethane foam, while improving its mechanical properties and stability to meet actual use needs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a composite amine catalyst, which comprises the following raw materials, calculated by mass percentage: 18-50% of tertiary amine, 3-5% of organic acid, 3-15% of 1,8-diazabicyclo[5.4.0]undec-7-ene salt and 44-62% of small molecule polyol; the tertiary amine comprises triethylenediamine and enhanced tertiary amine. The composite amine catalyst proposed by the invention, when applied to the preparation of low-density elastic polyurethane foam, can significantly reduce the compression permanent deformation of the low-density elastic polyurethane foam under the premise of improving the mechanical properties of the low-density elastic polyurethane foam, so as to overcome the shortcomings in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, in particular to a complex amine catalyst and a preparation method and application thereof. Background Art

[0002] Soft polyurethane foam is widely used in bedding and seating due to its excellent shock absorption and comfort. Soft polyurethane foam is mainly divided into slow-rebound polyurethane foam and elastic polyurethane foam. Compared with slow-rebound polyurethane foam, elastic polyurethane foam is lighter and softer, and has good rapid rebound ability. The above characteristics make elastic polyurethane foam more widely used and studied. For easy transportation and storage, elastic polyurethane foam is often compressed and packaged. Therefore, the ideal elastic polyurethane foam should have the characteristics of low compression permanent deformation to ensure that after long-term compression, once the external force is released, it can quickly and almost completely recover to its original size.

[0003] The preparation of elastic polyurethane foam involves two reactions: blowing and gelling. In the blowing reaction, isocyanate reacts with water to generate urea segments and carbon dioxide gas. The carbon dioxide gas expands to form bubble nuclei and eventually grows into bubbles, making the elastic polyurethane foam present a foam-like structure. In the gelling reaction, isocyanate reacts with polyether polyol to generate carbamate segments. The carbamate segments construct the network structure of polyurethane foam and provide excellent physical and chemical properties. In addition, polyurethane foam is a block copolymer composed of urea segments and carbamate segments. The raw materials isocyanate and water have small molecular weights, so the urea segments generated by the reaction are shorter; while the molecular weight of polyether polyol is large, and the carbamate segments generated by its reaction with isocyanate are longer. Both urea segments and carbamate segments contain atoms and groups with strong electronegativity, which enable both to form hydrogen bonds. However, the shorter urea segments make their hydrogen bond formation ability strong and concentrated; in contrast, the hydrogen bonds in the carbamate segments are sparse because they are diluted by the polyether segments. In addition, although hydrogen bonds can enhance mechanical properties, their reversibility makes them prone to creep under long-term compression, resulting in the inability of the polyurethane foam to fully recover its shape and permanent compression deformation.

[0004] In addition, when the density of elastic polyurethane foam reaches or exceeds 35kg / m 3 In order to increase its density, it is necessary to increase the polyether polyol in the formula to promote the formation of a network structure. The above measures make the block copolymers that make up the elastic polyurethane foam have more urethane segments, which reduces the number of hydrogen bonds and makes it relatively easy to achieve low compression permanent deformation. However, when the density is reduced to 30kg / m 3When the unit density is 0.04 or below, in order to reduce the unit density, it is usually necessary to increase the amount of water in the formula to promote foaming during the preparation process. However, the above measures lead to the formation of more concentrated urea segments in the block copolymers that constitute the elastic polyurethane foam. The concentrated distribution of urea segments leads to the formation of more hydrogen bonds, which makes the compression permanent deformation of the low-density elastic polyurethane foam larger and difficult to meet the actual use requirements.

[0005] At present, in order to solve the technical problem of large compression permanent deformation of low-density elastic polyurethane foam, the industry has also mainly improved the catalyst and the raw materials of elastic polyurethane foam, such as polyether polyol components and isocyanate, to reduce the compression permanent deformation of elastic polyurethane foam. However, due to the influence of factors such as the selection of raw materials and the preparation process, the degree of reduction of the compression permanent deformation of elastic polyurethane foam is limited, and it is still difficult to meet the actual use needs. Summary of the invention

[0006] One of the purposes of the present invention is to provide a composite amine catalyst, which, when used to prepare low-density elastic polyurethane foam, can significantly reduce the compression permanent deformation of the low-density elastic polyurethane foam while improving the mechanical properties of the low-density elastic polyurethane foam, so as to overcome the shortcomings of the prior art.

[0007] The second object of the present invention is to provide a method for preparing a composite amine catalyst. The preparation method is simple and easy to operate, and ensures that when the obtained composite amine catalyst is used to prepare a low-density elastic polyurethane foam, the compression permanent deformation of the low-density elastic polyurethane foam can be significantly reduced while improving the mechanical properties of the low-density elastic polyurethane foam.

[0008] The third object of the present invention is to provide an application of a complex amine catalyst, which, when used to prepare a low-density elastic polyurethane foam, can significantly reduce the compression permanent deformation of the low-density elastic polyurethane foam while improving the mechanical properties of the low-density elastic polyurethane foam.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] A composite amine catalyst, calculated by mass percentage, comprises the following raw materials: 18-50% of tertiary amine, 3-5% of organic acid, 3-15% of 1,8-diazabicyclo[5.4.0]undec-7-ene salt and 44-62% of small molecule polyol;

[0011] The tertiary amines include triethylenediamine and enhanced tertiary amines.

[0012] Furthermore, the following raw materials are included, calculated by mass percentage: 38% of tertiary amine, 4% of organic acid, 6% of 1,8-diazabicyclo[5.4.0]undec-7-ene salt and 52% of small molecule polyol.

[0013] Furthermore, calculated by mass ratio, the mixing ratio of the triethylenediamine and the enhanced tertiary amine is (1-5):1.

[0014] Furthermore, the enhanced tertiary amine includes any one or more combinations of bis(dimethylamino)ethyl ether, dimethylaminoethoxyethanol, pentamethyldiethylenetriamine, tetramethyldipropylenetriamine, dimethylaminopropylamine diisopropyl alcohol and 2,2,4-trimethyl-2-silamorpholine.

[0015] Further, the 1,8-diazabicyclo[5.4.0]undec-7-ene salt includes any one of 1,8-diazabicyclo[5.4.0]undec-7-enecarboxylate, 1,8-diazabicyclo[5.4.0]undec-7-eneisooctanoate and 1,8-diazabicyclo[5.4.0]undec-7-enephenolate.

[0016] Furthermore, the small molecule polyol includes any one of a small molecule diol and a small molecule triol.

[0017] Further, the small molecule diol includes any one of dipropylene glycol and diethylene glycol;

[0018] The small molecule triol includes any one of propylene glycol and triisopropanolamine.

[0019] Furthermore, the organic acid includes any one of formic acid and isooctanoic acid.

[0020] A method for preparing a composite amine catalyst, used for preparing the composite amine catalyst, comprises the following steps:

[0021] A. Add the formulated amount of triethylenediamine to the small molecule polyol, and heat and stir to obtain a mixed solution;

[0022] B. Add the formulated amount of organic acid, enhanced tertiary amine compound and 1,8-diazabicyclo[5.4.0]undec-7-ene salt to the mixed solution in sequence, heat and stir, and cool to obtain a composite amine catalyst.

[0023] An application of a composite amine catalyst in preparing a low-density elastic polyurethane foam, using the composite amine catalyst as claimed in claim 1, and the application method is as follows: calculated by weight, the low-density elastic polyurethane foam formula includes 50-65 parts of polypropylene glycol with a molecular weight of 3000, 15-17 parts of polymer polyether polyol, 2-3 parts of water, 0.1-0.3 parts of the composite amine catalyst, 0.05-0.07 parts of stannous octoate and 25-38 parts of TDI80;

[0024] After uniformly mixing the formulated amount of polypropylene glycol with a molecular weight of 3000, polymer polyether polyol, water and complex amine catalyst, adding the formulated amount of stannous octoate and TDI80, and continuing to stir for 3 to 4 seconds to obtain a mixture; pouring the mixture into a paper box, performing foaming and aging in sequence, to obtain a low-density elastic polyurethane foam.

[0025] The technical solution provided by the present invention may include the following beneficial effects:

[0026] 1. By utilizing the difference in the activity of the composite amine catalyst on the blowing reaction and the gel reaction, the progress of the blowing reaction and the gel reaction is regulated, so that the carbamate segment and the urea segment form a suitable distribution in the block copolymer, avoiding the excessive concentration of the urea segment and causing too many hydrogen bonds, resulting in excessive compression permanent deformation of the low-density elastic polyurethane foam. At the same time, the catalyst can also effectively adjust the number and distribution of cross-linking points in the block copolymer and build a tighter network structure. The above network structure not only weakens the creep effect of hydrogen bonds, further reduces the compression permanent deformation of the low-density elastic polyurethane foam, but also avoids the stress concentration problem caused by the local over-density of the cross-linking points, thereby improving the overall performance and stability of the low-density elastic polyurethane foam.

[0027] 2. This technical solution adds small molecule polyols to the formula of the complex amine catalyst. Compared with polyether polyols, small molecule polyols have a lower molecular weight and contain a higher proportion of hydroxyl functional groups, thus showing higher gel reaction activity under the same conditions. At the same time, the steric hindrance of its hydroxyl group is small and it is easier to react with isocyanate groups. The above two characteristics enable small molecule polyols to adjust the distribution of crosslinking points in block copolymers, which is not only conducive to building a tighter network structure, thereby limiting the movement of molecular chains, thereby weakening the creep effect of hydrogen bonds, and reducing the compression permanent deformation of low-density elastic polyurethane foams, but also effectively disperse the stress under the action of external forces, reduce the hydrogen bond breakage caused by stress concentration, thereby maintaining the stability of hydrogen bonds, and then reducing the creep effect, which is also conducive to reducing the compression permanent deformation of low-density elastic polyurethane foams. In addition, by limiting the addition amount of small molecule polyols in the complex amine catalyst to within the range of 44% to 62%, and using its high addition amount to adjust the number of crosslinking points in the block copolymer, a tighter network structure can also be constructed to reduce compression permanent deformation. DETAILED DESCRIPTION

[0028] The technical solution provides a composite amine catalyst, which includes the following raw materials, calculated by mass percentage: 18-50% of tertiary amine, 3-5% of organic acid, 3-15% of 1,8-diazabicyclo[5.4.0]undec-7-ene salt and 44-62% of small molecule polyol;

[0029] The tertiary amines include triethylenediamine and enhanced tertiary amines.

[0030] In view of the technical problem of large compression permanent deformation of low-density elastic polyurethane foam in the prior art, the present technical solution proposes a composite amine catalyst. By optimizing the ratio design and raw material optimization of the composite amine catalyst, when it is used to prepare low-density elastic polyurethane foam, the mechanical properties of the low-density elastic polyurethane foam can be improved while significantly reducing the compression permanent deformation of the low-density elastic polyurethane foam to meet actual use needs.

[0031] Specifically, the technical solution regulates the progress of the blowing reaction and the gel reaction by utilizing the activity difference of the composite amine catalyst to the blowing reaction and the gel reaction, so that the carbamate segment and the urea group segment form a suitable distribution in the block copolymer, and avoid the excessive concentration of the urea group segment and the excessive number of hydrogen bonds, resulting in the problem of excessive compression permanent deformation of the low-density elastic polyurethane foam. At the same time, the catalyst can also effectively regulate the number and distribution of cross-linking points in the block copolymer, and build a tighter network structure. The above network structure not only weakens the creep effect of hydrogen bonds, but also further reduces the compression permanent deformation of the low-density elastic polyurethane foam, and can also avoid the stress concentration problem caused by the local over-density of the cross-linking points, thereby improving the overall performance and stability of the low-density elastic polyurethane foam. In addition, the blowing reaction activity and gel reaction activity of the composite amine catalyst of the technical solution are suitable, so that the low-density elastic polyurethane foam prepared by using it has foam stability and suitable density, which is conducive to ensuring its performance. It should be noted that in the preparation process of elastic polyurethane foam, the dosage of polyether polyol, water and isocyanate is set to a fixed value, and isocyanate is usually in an excess state, so that the number of carbamate segments and urea segments in the final product is basically determined.

[0032] More specifically, the raw materials of the composite amine catalyst in the technical solution include tertiary amine, organic acid and 1,8-diazabicyclo[5.4.0]undec-7-ene salt; the tertiary amine includes triethylenediamine and enhanced tertiary amine. Among them, triethylenediamine has less hindrance on its nitrogen atom, making the hydroxyl group in the polyether polyol easily accessible, thereby showing higher gel reaction activity. The enhanced tertiary amine can effectively regulate the blowing reaction and gel reaction activity of the composite amine catalyst.

[0033] Organic acids are acidic and can be neutralized with alkaline tertiary amines to form salt structures of nitrogen atoms on the tertiary amines, thereby changing their electron cloud distribution and adjusting the reaction activity of the blow-drying and gelling reactions at different stages.

[0034] 1,8-diazabicyclo[5.4.0]undec-7-ene, as a bicyclic amidine compound, has strong blowing reaction and gel reaction activity, and its activity increases significantly with increasing temperature. However, its excessive activity may lead to too short reaction time, affecting the convenience of actual production. Therefore, this scheme uses a closed 1,8-diazabicyclo[5.4.0]undec-7-ene salt to ensure its moderate catalytic activity.

[0035] Although the combination of tertiary amine, organic acid and 1,8-diazabicyclo[5.4.0]undec-7-ene salt can regulate the progress of blowing reaction and gel reaction by the difference in activity of blowing reaction and gel reaction, so that the carbamate segment and urea segment form a suitable distribution in the block copolymer, thereby improving the compression permanent deformation problem of low-density elastic polyurethane foam, it still cannot meet the occasions where the compression permanent deformation requirements of low-density elastic polyurethane foam are high. Therefore, the technical solution adds small molecule polyols to the composite amine catalyst formula. Compared with polyether polyols, small molecule polyols have a lower molecular weight and contain a higher proportion of hydroxyl functional groups, thus showing higher gel reaction activity under the same conditions. At the same time, the steric hindrance of its hydroxyl group is smaller, and it is easier to react with isocyanate groups. The above two characteristics enable small molecule polyols to adjust the distribution of crosslinking points in block copolymers, which is not only conducive to building a tighter network structure, thereby limiting the movement of molecular chains, thereby weakening the creep effect of hydrogen bonds, and reducing the compression permanent deformation of low-density elastic polyurethane foams, but also effectively disperse the stress under the action of external forces, reduce the hydrogen bond breakage caused by stress concentration, thereby maintaining the stability of hydrogen bonds, and then reducing the creep effect, which is also conducive to reducing the compression permanent deformation of low-density elastic polyurethane foams. In addition, by limiting the addition amount of small molecule polyols in the complex amine catalyst to within the range of 44% to 62%, using its high addition amount to adjust the number of crosslinking points in the block copolymer, it is also possible to build a tighter network structure and reduce compression permanent deformation.

[0036] In addition, regulating the number and distribution of cross-linking points in block copolymers by using small molecule polyols is also helpful in avoiding stress concentration problems caused by local over-density of cross-linking points, thereby improving the overall performance and stability of low-density elastic polyurethane foam.

[0037] Therefore, the technical solution combines tertiary amines, organic acids, 1,8-diazabicyclo[5.4.0]undec-7-ene salts and small molecule polyols, and limits the amount of small molecule polyols added, so that the low-density elastic polyurethane foam prepared using the composite amine catalyst of the technical solution can not only effectively reduce the number of hydrogen bonds while improving the performance, but also weaken the creep effect of hydrogen bonds, thereby reducing the compression permanent deformation of the low-density elastic polyurethane foam.

[0038] It should be noted that the technical solution cannot simply rely on enhancing the activity of the gel reaction to enhance the density of the network structure, thereby changing the creep effect that weakens the hydrogen bonds, and then improving the compression permanent deformation of the low-density elastic polyurethane foam. The reason is that in the blowing reaction, the bubble nuclei are continuously generated in the system and collide and fuse with each other, gradually forming larger bubbles. At the same time, the urea segments generated by the blowing reaction and the carbamate segments generated by the gel reaction are distributed around the bubbles to construct the supporting skeleton of the bubbles. If the gel reaction rate is too fast and the blowing reaction is insufficient, the foam rises slowly, and the system cannot generate enough gas pressure to form sufficient bubbles before it is fully cured, which causes the elastic polyurethane foam to be too dense and the target product cannot be obtained.

[0039] It should be further explained that triethylenediamine is solid, and small molecule polyols can be used as its solvent, which is conducive to ensuring the stability of the performance of the obtained complex amine catalyst. In addition, 1,8-diazabicyclo[5.4.0]undec-7-ene is easy to react with carbon dioxide, moisture, etc. in the air, resulting in performance degradation. The technical solution uses a closed 1,8-diazabicyclo[5.4.0]undec-7-ene salt, which is conducive to improving its stability and extending the shelf life.

[0040] It is further explained that, calculated by mass percentage, the following raw materials are included: 38% of tertiary amine, 4% of organic acid, 6% of 1,8-diazabicyclo[5.4.0]undec-7-ene salt and 52% of small molecule polyol.

[0041] By further optimizing the ratio of raw materials in the complex amine catalyst, the performance of the complex amine catalyst can be optimized, so that the low-density elastic polyurethane foam has a lower compression permanent deformation.

[0042] It is further described that, calculated by mass ratio, the mixing ratio of the triethylenediamine and the enhanced tertiary amine is (1-5):1.

[0043] The mixing ratio of triethylenediamine and enhanced tertiary amine is (1-5):1, which is beneficial to regulating the blowing reaction activity and gel reaction activity of the composite amine catalyst and ensuring its performance.

[0044] It is further described that the enhanced tertiary amine includes any one or more combinations of bis(dimethylamino)ethyl ether, dimethylaminoethoxyethanol, pentamethyldiethylenetriamine, tetramethyldipropylenetriamine, dimethylaminopropylamine diisopropyl alcohol and 2,2,4-trimethyl-2-silamorpholine.

[0045] By optimizing the types of enhanced tertiary amines, and the preferred enhanced tertiary amines have high cost performance, it is not only beneficial to select suitable raw materials according to actual needs and improve the flexibility of the formulation, but also beneficial to save production costs while ensuring the performance of the complex amine catalyst.

[0046] It is further described that the 1,8-diazabicyclo[5.4.0]undec-7-ene salt includes any one of 1,8-diazabicyclo[5.4.0]undec-7-enecarboxylate, 1,8-diazabicyclo[5.4.0]undec-7-eneisooctanoate and 1,8-diazabicyclo[5.4.0]undec-7-enephenolate.

[0047] By optimizing the types of 1,8-diazabicyclo[5.4.0]undec-7-ene salts, it is beneficial to select suitable raw materials according to actual needs, improve the flexibility of the formulation, and expand the application range of the complex amine catalyst.

[0048] The preparation method of 1,8-diazabicyclo[5.4.0]undec-7-enecarboxylate is as follows: ethylene glycol and 1,8-diazabicyclo[5.4.0]undec-7-ene are sequentially added to a reaction vessel, stirred and heated to 40°C, maintained for 0.5h, and then formic acid is added dropwise. After the addition is completed, the temperature is kept at 60°C for 6h, and 1,8-diazabicyclo[5.4.0]undec-7-enecarboxylate is obtained after cooling.

[0049] The preparation method of 1,8-diazabicyclo[5.4.0]undec-7-ene isooctanoic acid salt is as follows: ethylene glycol and 1,8-diazabicyclo[5.4.0]undec-7-ene are sequentially added into a reaction container, stirred and heated to 40°C, and then isooctanoic acid is added dropwise. After the addition is completed, the temperature is kept at 60°C for 6 hours, and 1,8-diazabicyclo[5.4.0]undec-7-ene isooctanoic acid salt is obtained after cooling.

[0050] The preparation method of 1,8-diazabicyclo[5.4.0]undec-7-enephenolate is as follows: ethylene glycol and 1,8-diazabicyclo[5.4.0]undec-7-ene are sequentially added into a reaction container, stirred and heated to 40°C, and then isooctanoic acid is added dropwise. After the addition is completed, the temperature is kept at 50°C for 6 hours, and 1,8-diazabicyclo[5.4.0]undec-7-enephenolate is obtained after cooling.

[0051] It is further explained that the small molecule polyol includes any one of a small molecule diol and a small molecule triol.

[0052] Both small molecule diols and small molecule triols can effectively regulate the number and distribution of crosslinking points in block copolymers, build a tighter network structure, and thereby weaken the creep effect of hydrogen bonds. In addition, both small molecule diols and small molecule triols can be used as solvents to dissolve triethylene diamine. Therefore, the technical solution preferably uses any one of small molecule diols and small molecule triols as the type of small molecule polyols, which is not only conducive to selecting suitable raw materials according to actual needs, improving the flexibility of the formula, but also conducive to ensuring the performance of the complex amine catalyst.

[0053] It is further described that the small molecule diol includes any one of dipropylene glycol and diethylene glycol;

[0054] The small molecule triol includes any one of propylene glycol and triisopropanolamine.

[0055] Dipropylene glycol, diethylene glycol, glycerol and triisopropanolamine can not only effectively regulate the number and distribution of crosslinking points in block copolymer, build a tighter network structure, so as to weaken the creep effect of hydrogen bonds, and can also be used as a solvent to dissolve triethylene diamine. In addition, dipropylene glycol, diethylene glycol, glycerol and triisopropanolamine are all cost-effective, and raw materials are easy to obtain. Therefore, the technical solution is preferably any one of dipropylene glycol and diethylene glycol by small molecule diols, and is preferably any one of glycerol and triisopropanolamine by small molecule triols, which is conducive to saving production costs under the premise of ensuring the performance of complex amine catalysts.

[0056] It is further specified that the organic acid includes any one of formic acid and isooctanoic acid.

[0057] Both formic acid and isooctanoic acid are acidic and can be neutralized with alkaline tertiary amines to form a salt structure with nitrogen atoms on the tertiary amines, thereby changing its electron cloud distribution and adjusting the reactivity of the blowing reaction and the gel reaction at different stages. Therefore, the technical solution preferably selects any one of formic acid and isooctanoic acid as the organic acid, which is conducive to ensuring the performance of the composite amine catalyst.

[0058] A method for preparing a composite amine catalyst, used for preparing the composite amine catalyst, comprises the following steps:

[0059] A. Add the formulated amount of triethylenediamine to the small molecule polyol, and heat and stir to obtain a mixed solution;

[0060] B. Add the formulated amount of organic acid, enhanced tertiary amine compound and 1,8-diazabicyclo[5.4.0]undec-7-ene salt to the mixed solution in sequence, heat and stir, and cool to obtain a composite amine catalyst.

[0061] The technical scheme also proposes a preparation method of a composite amine catalyst, which is simple and easy to operate, ensuring that when the obtained composite amine catalyst is used to prepare low-density elastic polyurethane foam, it can significantly reduce the compression permanent deformation of the low-density elastic polyurethane foam while improving the performance of the low-density elastic polyurethane foam.

[0062] Specifically, since triethylenediamine is solid, it needs to be added into the small molecule polyol, heated and stirred to dissolve the triethylenediamine and then mixed with other raw materials.

[0063] Preferably, in step A, the heating temperature of the heating and stirring is 35 to 40° C., and the heating time is 0.2 to 0.5 h;

[0064] In step B, the heating temperature of the heating and stirring is 40-60° C., and the heating time is 7-8 hours.

[0065] The technical solution limits the heating temperature and heating time of heating and stirring in step A and step B, which is beneficial to reducing side reactions and improving the purity of the product.

[0066] The invention discloses an application of a composite amine catalyst in preparing a low-density elastic polyurethane foam. The composite amine catalyst is used in the following application method: the low-density elastic polyurethane foam formula comprises, by weight, 50-65 parts of polypropylene glycol with a molecular weight of 3000, 15-17 parts of polymer polyether polyol, 2-3 parts of water, 0.1-0.3 parts of the composite amine catalyst, 0.05-0.07 parts of stannous octoate and 25-38 parts of TDI80;

[0067] After uniformly mixing the formulated amount of polypropylene glycol with a molecular weight of 3000, polymer polyether polyol, water and complex amine catalyst, adding the formulated amount of stannous octoate and TDI80, and continuing to stir for 3 to 4 seconds to obtain a mixture; pouring the mixture into a paper box, performing foaming and aging in sequence, to obtain a low-density elastic polyurethane foam.

[0068] The technical solution also proposes the use of a composite amine catalyst in the preparation of low-density elastic polyurethane foam. The prepared low-density elastic polyurethane foam can significantly reduce the compression permanent deformation of the low-density elastic polyurethane foam while improving the mechanical properties.

[0069] It should be noted that, calculated by mass percentage, TDI80 includes 80% of 2,4-toluene diisocyanate and 20% of 2,6-toluene diisocyanate. In addition, the polymer polyether polyol is prepared by free graft polymerization of polyether polyol, acrylonitrile and styrene monomers, and calculated by mass percentage, the solid content of the polymer polyether polyol is 45%.

[0070] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0071] Performance Testing:

[0072] (1) Rising time: The time starts when TDI80 is added, and the time when the foam starts to rise.

[0073] (2) Bubble time: The timing starts when TDI80 is added, and the time when bubbles appear on the foam surface.

[0074] (3) Density: Tested according to the test method of GBT6343-1995 Determination of apparent density of foam plastics and rubber.

[0075] (4) Hardness: After peeling the low-density elastic polyurethane foam material, cut it into 300×300×50mm samples and place the samples on a flat surface. Use an LX-F hardness tester to measure the hardness of 5 points on the sample at least 25mm apart. Take the average value of the hardness test results as the hardness value of the low-density elastic polyurethane foam.

[0076] (5) Air permeability: The air permeability is measured using a homemade device consisting of an air compressor, an air flow meter, a glass U-tube, and a stainless steel pressure head with an inner diameter of 20 mm. The low-density elastic polyurethane foam is cut into 300×300×50 mm samples, and the air compressor cylinder pressure is adjusted to 0.7-0.75 mPa; the air flow meter is adjusted so that the water level reading of the U-tube is 300 mm; the pressure head is placed on the surface of the horizontally placed sample and the water level reading of the U-tube is recorded; the air permeability is measured at 5 points at different locations on the sample at least 100 mm apart, and the average value of the air permeability test results is taken as the air permeability of the low-density elastic polyurethane foam. The larger the value, the worse the air permeability of the low-density elastic polyurethane foam.

[0077] (6) Tensile strength: tested according to the test method in GB / T6669-2008 Determination of tensile strength and elongation at break of flexible foam polymer materials.

[0078] (7) Elongation at break: The test is conducted according to the test method in GB / T6669-2008 Determination of tensile strength and elongation at break of flexible foam polymer materials.

[0079] (8) Compression set: The test is conducted according to the test method in GB 6669-2008 Determination of compression set of flexible foam polymeric materials.

[0080] Example 1

[0081] A. Add 28% triethylenediamine to 52% dipropylene glycol, and stir at 40°C for 0.2h to obtain a mixed solution;

[0082] B. Add 4% formic acid, 10% dimethylaminoethoxyethanol and 6% 1,8-diazabicyclo[5.4.0]undec-7-enecarboxylate into the mixed solution in sequence, stir at 35°C for 7 hours, and obtain a composite amine catalyst after cooling.

[0083] Example 2

[0084] A. Add 25% triethylenediamine to 55% diethylene glycol, and stir at 35°C for 0.3h to obtain a mixed solution;

[0085] B. Add 5% of isooctanoic acid, 10% of tetramethyldipropylenetriamine and 5% of 1,8-diazabicyclo[5.4.0]undec-7-ene isooctanoate to the mixed solution in sequence, stir at 38°C for 8 hours, and obtain a composite amine catalyst after cooling.

[0086] Example 3

[0087] A. Add 30% triethylenediamine to 48% propylene glycol, and stir at 38°C for 0.5h to obtain a mixed solution;

[0088] B. Add 4% of isooctanoic acid, 8% of dimethylaminopropylamine diisopropyl alcohol and 10% of 1,8-diazabicyclo[5.4.0]undec-7-enephenolate to the mixed solution in sequence, stir at 40°C for 7.5 hours, and obtain a composite amine catalyst after cooling.

[0089] Example 4

[0090] A. Add 25% triethylenediamine to 50% triisopropanolamine, and stir at 40°C for 0.4h to obtain a mixed solution;

[0091] B. Add 5% formic acid, 9% pentamethyldiethylenetriamine, 3% 2,2,4-trimethyl-2-silamorpholine and 11% 1,8-diazabicyclo[5.4.0]undec-7-ene isooctanoate into the mixed solution in sequence, stir at 40°C for 7 hours, and obtain a composite amine catalyst after cooling.

[0092] Example 5

[0093] A. Add 20% triethylenediamine to 50% dipropylene glycol, and stir at 37°C for 0.5h to obtain a mixed solution;

[0094] B. Add 5% of isooctanoic acid, 15% of bis(dimethylaminoethyl)ether and 10% of 1,8-diazabicyclo[5.4.0]undec-7-enecarboxylate into the mixed solution in sequence, stir at 38°C for 8 hours, and obtain a composite amine catalyst after cooling.

[0095] Comparative Example 1

[0096] Comparative Example 1 has the same preparation method and raw materials as Example 1, except that no small molecule polyol is added in Comparative Example 1. That is, the composite amine catalyst has the following raw materials calculated by mass percentage: 50% triethylenediamine, 20% formic acid, 20% dimethylaminoethoxyethanol and 10% 1,8-diazabicyclo[5.4.0]undec-7-enecarboxylate.

[0097] Comparative Example 2

[0098] Comparative Example 2 uses the composite amine catalyst PUCAT AN-1. Calculated by weight percentage, the composite amine catalyst PUCAT AN-1 includes 70% of bis(dimethylaminoethyl) ether and 30% of dipropylene glycol.

[0099] Comparative Example 3

[0100] Comparative Example 3 uses the composite amine catalyst PUCAT L-33. Calculated by mass percentage, the composite amine catalyst PUCAT L-33 includes 33% triethylenediamine and 67% dipropylene glycol.

[0101] The low-density elastic polyurethane foam is prepared using the composite amine catalyst obtained in the embodiment and the comparative example. The specific preparation method is: after evenly mixing 50 parts of polypropylene glycol with a molecular weight of 3000, 15 parts of polymer polyether polyol, 2 parts of water and 0.2 parts of the composite amine catalyst, 0.05 parts of stannous octoate and 25 parts of TDI80 are added, and stirring is continued for 3 to 4 seconds to obtain a mixture; the mixture is poured into a paper box for foaming and aging in sequence to obtain a low-density elastic polyurethane foam. The low-density elastic polyurethane foam prepared using the composite amine catalyst in the embodiment and the comparative example is subjected to a performance test, and the specific test method results are shown in Table 1 below:

[0102] Table 1 Test results of relevant properties of low-density elastic polyurethane foam

[0103] Experiment number Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Start time(S) 10.6 11.3 9.1 8.6 8.5 8.6 6.5 11.7 Bubble Time(S) 103 108.6 91.6 87.7 87.1 101 75.1 105.4 Air permeability(mm) 360 370 440 309 440 1200 330 820 Surface hardness (HS) 81 77 79 78 79 74 60 75 <![CDATA[Density (kg / m 3 )]]> 29.8 29.2 29.6 29.4 30.2 29.2 28.1 29.6 Elongation at break (%) 105 96 101 99 98 72 92 93 Tensile strength(kPa) 86 82.6 83.3 82.1 81.6 79.2 77.7 78 Compression set (%) 5.40% 4.90% 6.50% 7.60% 7.30% 14.50% 25.20% 15.70%

[0104] It can be seen from the performance test results in the above table that the surface hardness, elongation at break and tensile strength and other mechanical performance test indicators of the low-density elastic polyurethane foam prepared by using the composite amine catalyst obtained in the embodiment of the present technical scheme are superior to the surface hardness, elongation at break and tensile strength and other mechanical performance test indicators of the low-density elastic polyurethane foam prepared by using the composite amine catalyst obtained in the comparative example. The low-density elastic polyurethane foam prepared by using the composite amine catalyst obtained by the present technical scheme can significantly reduce the compression permanent deformation of the low-density elastic polyurethane foam while improving the mechanical properties.

[0105] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.

Claims

1. A complex amine catalyst, characterized in that: Calculated by mass percentage, the raw materials include: 18-50% of tertiary amine, 3-5% of organic acid, 3-15% of 1,8-diazabicyclo[5.4.0]undec-7-ene salt and 44-62% of small molecule polyol; The tertiary amines include triethylenediamine and enhanced tertiary amines.

2. A complex amine catalyst according to claim 1, characterized in that: Calculated by mass percentage, the raw materials include: 38% of tertiary amine, 4% of organic acid, 6% of 1,8-diazabicyclo[5.4.0]undec-7-ene salt and 52% of small molecule polyol.

3. A complex amine catalyst according to claim 1, characterized in that: Calculated by mass ratio, the mixing ratio of the triethylenediamine and the enhanced tertiary amine is (1-5):

1.

4. A complex amine catalyst according to claim 1, characterized in that: The enhanced tertiary amine includes any one or more combinations of bis(dimethylamino)ethyl ether, dimethylaminoethoxyethanol, pentamethyldiethylenetriamine, tetramethyldipropylenetriamine, dimethylaminopropylamine diisopropyl alcohol and 2,2,4-trimethyl-2-silamorpholine.

5. A complex amine catalyst according to claim 1, characterized in that: The 1,8-diazabicyclo[5.4.0]undec-7-ene salt includes any one of 1,8-diazabicyclo[5.4.0]undec-7-enecarboxylate, 1,8-diazabicyclo[5.4.0]undec-7-eneisooctanoate and 1,8-diazabicyclo[5.4.0]undec-7-enephenolate.

6. A complex amine catalyst according to claim 1, characterized in that: The small molecule polyol includes any one of a small molecule diol and a small molecule triol.

7. A complex amine catalyst according to claim 1, characterized in that: The small molecule diol includes any one of dipropylene glycol and diethylene glycol; The small molecule triol includes any one of propylene glycol and triisopropanolamine.

8. A complex amine catalyst according to claim 1, characterized in that: The organic acid includes any one of formic acid and isooctanoic acid.

9. A method for preparing a complex amine catalyst, characterized in that: The method for preparing the composite amine catalyst according to claims 1 to 8 comprises the following steps: A. Add the formulated amount of triethylenediamine to the small molecule polyol, and heat and stir to obtain a mixed solution; B. Add the formulated amount of organic acid, enhanced tertiary amine compound and 1,8-diazabicyclo[5.4.0]undec-7-ene salt to the mixed solution in sequence, heat and stir, and cool to obtain a composite amine catalyst.

10. Use of a complex amine catalyst in preparing low-density elastic polyurethane foam, characterized in that: Using a composite amine catalyst as described in any one of claims 1 to 8, the application method is as follows: calculated by weight, the low-density elastic polyurethane foam formula includes 50 to 65 parts of polypropylene glycol with a molecular weight of 3000, 15 to 17 parts of polymer polyether polyol, 2 to 3 parts of water, 0.1 to 0.3 parts of composite amine catalyst, 0.05 to 0.07 parts of stannous octoate and 25 to 38 parts of TDI80; After uniformly mixing the formulated amount of polypropylene glycol with a molecular weight of 3000, polymer polyether polyol, water and complex amine catalyst, adding the formulated amount of stannous octoate and TDI80, and continuing to stir for 3 to 4 seconds to obtain a mixture; pouring the mixture into a paper box, performing foaming and aging in sequence, to obtain a low-density elastic polyurethane foam.